Promoting Stair Climbing: Intervention Effects Generalize to a Subsequent Stair Ascent - Webb, Oliver J.; Eves, Frank F. (American journal of health promotion, 2007)
Purpose. Studies report a significant increase in stair use when message prompts are introduced at the “point of choice” between stairs and escalators. Climbing one set of stairs, however, will not confer meaningful health dividends. Therefore, this study examined whether exposure to point of choice prompts also encouraged individuals to climb the next set of stairs that they encountered. Design. Interrupted time-series design. Settings. Two separate stair/escalator pairings within a U.K. shopping mall (the “intervention” site and the “generalization” site), separated by a 25-m long atrium. Subjects. Ascending pedestrians (intervention site n = 29,713; generalization site n = 47,553). Interventions. Two weeks of baseline monitoring were followed by a 13-week intervention in which banners carrying health promotion messages were introduced at the intervention site only. Measures. At both sites observers inconspicuously recorded pedestrians' methods of ascent, along with their gender, age, ethnicity, and baggage. Results. Banners increased stair climbing at the intervention site by 161%. Results also suggested a simultaneous increase of up to 143% at the generalization site, where no prompt was in place. At both sites stair use remained significantly elevated 5 weeks after the banners were removed. Conclusions. It appears that exposure to point of choice prompts can encourage pedestrians to climb stairs when they are encountered in a subsequent setting. Consequently stair-climbing interventions are likely to engage the public in more physical activity than previously realized.